Determining ULF Wave Contributions to Geomagnetically Induced Currents: The Important Role of Sampling Rate - Michael D. Hartinger; Xueling Shi; Craig J. Rodger; Ikuko Fujii; E. Joshua Rigler; Karl Kappler; Jürgen Matzka; Jeffrey J. Love; Joseph B. H. Baker; Daniel H. Mac Manus; Michael Dalzell; Tanja Petersen (Space Weather)
Abstract Past studies found that large‐amplitude geomagnetically induced current (GIC) related to magnetospheric Ultra Low Frequency (ULF) waves tend to be associated with periods >120 s at magnetic latitudes >60°, with comparatively (a) smaller GIC amplitudes at lower latitudes and shorter wave periods and (b) fewer reports of waves associated with GIC at lower latitudes. ULF wave periods generally decrease with decreasing latitude; thus, we examine whether these trends might be due, in part, to the undersampling of ULF wave fields in commonly available measurements with 60 s sampling intervals. We use geomagnetic field (B), geoelectric field (E), and GIC measurements with 0.5–10 s sampling intervals during the 29–31 October 2003 geomagnetic storm to show that waves with periods <∼120 s were present during times with the largest amplitude E and GIC variations. These waves contributed to roughly half the maximum E and GIC values, including during times with the maximum GIC values reported over a 14‐year monitoring interval in New Zealand. The undersampling of wave periods <120 s in 60 s measurements can preclude identification of the cause of the GIC during some time intervals. These results indicate (a) ULF waves with periods ≤120 s are an important contributor to large amplitude GIC variations, (b) the use of 0.1–1.0 Hz sampling rates reveals their contributions to B, E, and GIC, and (c) these waves' contributions are likely strongest at magnetic latitudes <60° where ULF waves often have periods <120 s.